Medication adherence in older adults with hypertension in Slovakia - Mária, Sováriová Soósová; Valéria, Parová; Renáta, Suchanová; Antónia, Ulbrichtová; Olívia, Kopcová (Magyar Gerontológia, 2023)
Non-adherence to medical therapy in patients with arterial hypertension (AH) is associated with increased cardiovascular and cerebrovascular morbidity and mortality, and thus increased healthcare costs. The prevalence of AH increases with increasing age. In view of this, monitoring adherence to medical therapy in older adults and its determinants is very important.